Peculiarities in bioelectrical activity of muscles of the pelvic girdle and thigh in cases of hip joint pathology in adults - Kotulskiy, Igor; Dupliy, Diana; Isaeva, Natalya (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
Bioelectrical activity of the gluteus medius, great adductor and rectal femoral muscles at the moment of their maximal voluntary contraction was studied in 64 men with unilateral avascular necrosis of femoral head and in 18 men with unilateral coxarthrosis. As a control group, results of examination of 30 healthy men were used. It was revealed that in patients with avascular necrosis of femoral head the biopotential amplitude on the great adductor muscle of an affected limb was reliably higher (p < 0.01) and on the gluteus medius muscle lower (p < 0.01) versus muscles of an intact limb. In patients with coxarthrosis, this reciprocity disorder of bioelectrical activity was absent. The obtained data demonstrate a possible role, which central generator disorders of locomotion patterns play in pathogenesis of avascular necrosis of femoral head.